An updated checklist of the Odonata from Argentina - Von Ellenrieder, Natalia (2008)
An updated checklist of the Odonata spp. known to occur in Argentina is presented along with distributional information by province. 27 spp. are removed from previous listings, and 32 new records are added, bringing the total number of spp. to 271. Of the new records, 14 correspond to new spp. currently under description. The distribution of the 17 species presently known to be endemic to Argentina is mapped.